2021
DOI: 10.1371/journal.ppat.1009357
|View full text |Cite
|
Sign up to set email alerts
|

A diffusible signal factor of the intestine dictates Salmonella invasion through its direct control of the virulence activator HilD

Abstract: Successful intestinal infection by Salmonella requires optimized invasion of the gut epithelium, a function that is energetically costly. Salmonella have therefore evolved to intricately regulate the expression of their virulence determinants by utilizing specific environmental cues. Here we show that a powerful repressor of Salmonella invasion, a cis-2 unsaturated long chain fatty acid, is present in the murine large intestine. Originally identified in Xylella fastidiosa as a diffusible signal factor for quor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…HilD, HilC, and RtsA constitute a positive feed‐forward regulatory loop that controls SPI‐1. We previously showed that the intestinal long‐chain fatty acid c2‐HDA (Figure 1a) is a potent repressive fatty acid of SPI‐1 expression that binds directly to HilD (K d ~3.5 µM) (Bosire et al., 2020; Chowdhury et al., 2021). c2‐HDA can repress SPI‐1 expression in Salmonella Δ hilD mutants and diminish hilA expression that is driven individually by HilC or RtsA (Bosire et al., 2020), suggesting that these regulators may also be targets of c2‐HDA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HilD, HilC, and RtsA constitute a positive feed‐forward regulatory loop that controls SPI‐1. We previously showed that the intestinal long‐chain fatty acid c2‐HDA (Figure 1a) is a potent repressive fatty acid of SPI‐1 expression that binds directly to HilD (K d ~3.5 µM) (Bosire et al., 2020; Chowdhury et al., 2021). c2‐HDA can repress SPI‐1 expression in Salmonella Δ hilD mutants and diminish hilA expression that is driven individually by HilC or RtsA (Bosire et al., 2020), suggesting that these regulators may also be targets of c2‐HDA.…”
Section: Resultsmentioning
confidence: 99%
“…They are involved in intraspecies, interspecies, and interkingdom communication, by which they control motility, biofilm formation, antibiotic tolerance, persistence, and virulence (An & Tang, 2018; Beaulieu et al., 2013; Chandrasekaran et al., 2018; Ryan et al., 2015; Saffarian et al., 2019; Suppiger et al., 2016; Twomey et al., 2012). The DSF c2‐HDA is an exceptionally potent repressive compound of SPI‐1 expression and is present in the murine large intestine (Bosire et al., 2020; Chowdhury et al., 2021). It binds to HilD with high affinity and prevents it from binding to hilC and hilA promoters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that DSFs and other fatty acids inhibit key virulence mechanisms, such as planktonic growth, capsule production, and cell adhesion and induce biofilm dispersal in K. pneumoniae ( Rahmani-Badi et al, 2014 ; Gupta et al, 2020 ; Kumar et al, 2020 ). Chowdhury et al (2021) reported a cis -2-hexadecenoic acid (c2-HAD) DSF homolog encoding gene ( rpfF ) in Enterobacter sp. This DSF was proven to control the intestinal invasion of Salmonella sp.…”
Section: Biofilm and Qs Modulators In Acinetobacter Klebsiella And Enterobactermentioning
confidence: 99%
“…This DSF was proven to control the intestinal invasion of Salmonella sp. and control the main virulence regulon in this microorganism ( Chowdhury et al, 2021 ). c2-HAD is supposed to interfere also with the virulence of other intestinal gram-negative bacteria, including Enterobacter species.…”
Section: Biofilm and Qs Modulators In Acinetobacter Klebsiella And Enterobactermentioning
confidence: 99%